The activity of the dispatcher of the communication point of the fire and rescue unit in the conditions of the Arctic zone of the Russian Federation - Khlopovskikh Yu.G.; Korneychuk Ch.A.; Martinovich N.V.; Lomaeva T.A.; Fursov A.I. (Российская Арктика)
The article considers the features of the activity of the dispatcher of the communication point of the fire and rescue unit in the conditions of the Arctic zone of the Russian Federation. The characteristics of official activity due to the specifics of the climatic and ecological environment and their impact on the functional and psychological state of the dispatcher of the communication point of the unit are determined. Promising directions have been developed for optimizing the activities of the dispatcher of the communication point of the fire and rescue unit in the Arctic zone.